2016
DOI: 10.3389/fmicb.2016.01072
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activities of Bacteria Associated with the Brown Alga Padina pavonica

Abstract: Macroalgae belonging to the genus Padina are known to produce antibacterial compounds that may inhibit growth of human- and animal pathogens. Hitherto, it was unclear whether this antibacterial activity is produced by the macroalga itself or by secondary metabolite producing epiphytic bacteria. Here we report antibacterial activities of epiphytic bacteria isolated from Padina pavonica (Peacocks tail) located on northern coast of Tunisia. Eighteen isolates were obtained in pure culture and tested for antimicrob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 74 publications
(82 reference statements)
1
33
0
Order By: Relevance
“…This is because there are studies that have reported that seaweed-associated bacteria play crucial roles in the development and growth of seaweeds, showing a symbiotic relationship between the bacteria and the seaweeds [89]. Another study found a potential broad-spectrum antibacterial effect from epiphytic bacteria (Phylum: Firmicutes; closely related to Bacillus pumilus ) isolated from brown seaweed Padina pavonica, thus suggesting that bacteria associated with seaweeds might be producers of antibacterial compounds [90]. Recently, a study by Sujuliyani et al [91] showed that C. racemosa has symbiotic bacteria belonging to the genus Neisseria that is able to synthesize potential antibacterial compounds against S. aureus and Salmonella typhi .…”
Section: Discussionmentioning
confidence: 99%
“…This is because there are studies that have reported that seaweed-associated bacteria play crucial roles in the development and growth of seaweeds, showing a symbiotic relationship between the bacteria and the seaweeds [89]. Another study found a potential broad-spectrum antibacterial effect from epiphytic bacteria (Phylum: Firmicutes; closely related to Bacillus pumilus ) isolated from brown seaweed Padina pavonica, thus suggesting that bacteria associated with seaweeds might be producers of antibacterial compounds [90]. Recently, a study by Sujuliyani et al [91] showed that C. racemosa has symbiotic bacteria belonging to the genus Neisseria that is able to synthesize potential antibacterial compounds against S. aureus and Salmonella typhi .…”
Section: Discussionmentioning
confidence: 99%
“…Besides these studies Karthick et al (2015b) had reported on antimicrobial activity of certain seaweeds against pathogenic bacterial and fungal stains. Several authors suggested that macro algal associated bacteria were found to be an efficient producer of antimicrobial compounds ( Burgess et al, 1999 ; Lee et al, 2006 ; Kanagasabhapathy et al, 2008 ; Karthick et al, 2015a ; Ismail et al, 2016 ). On the other hand, certain brown algae also produced biologically active compounds which inhibited the settlement of bacterial colonies on the thallus ( Nagayama et al, 2002 ).…”
Section: Discussionmentioning
confidence: 99%
“…A relationship was found among the antimicrobial activity against S. aureus, E. coli, and C. albicans, and the FA docosapentaenoic (DPA, 22:5) and triacylglycerol contents [121]. In the green macroalga Ulva rigida, purified fractions of crude extracts with the highest antibacterial activity against S. aureus and Enterococcus faecalis comprised mainly 16:0, 18:1, and 16:1 n-7 FA [27]. Nevertheless, most of these studies neither isolated the predominant FA nor tested its activity.…”
Section: Fatty Acidsmentioning
confidence: 95%
“…The antimicrobial activity efficiency may be conditioned by seasonal variation, that must be related with shifts in the lipid profiles promoted by alterations in growth-related environmental conditions [118]. Nevertheless, a seasonal variation was not always verified, like in the green seaweed U. rigida that demonstrated a uniform antimicrobial activity throughout the year [27].…”
Section: Glycolipidsmentioning
confidence: 99%
See 1 more Smart Citation